1999
DOI: 10.1093/humrep/14.5.1217
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of follicle stimulating hormone may predict premature ovarian failure in FRAXA premutation women

Abstract: It is now recognized that female carriers of fragile X premutations are at increased risk of premature ovarian failure. We have studied 51 premenopausal women from fragile X families, to determine whether premutation carriers have variations in the hormonal markers of menopause, compared to full mutations and controls. We found a significant increase in serum follicle stimulating hormone in premutation carriers, suggesting that as a group they will enter menopause before full mutation carriers and unaffected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…16 In women who are still cycling we have demonstrated an increased level of serum FSH in the premutation group compared with controls. 13 In a small pilot study Braat et al 17 reported the hormonal profiles of nine premutation carriers under age 40 and found levels suggestive of ovarian failure in eight of them. Thus even in the absence of early menopause the premutation group appears to have the hormonal markers of ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In women who are still cycling we have demonstrated an increased level of serum FSH in the premutation group compared with controls. 13 In a small pilot study Braat et al 17 reported the hormonal profiles of nine premutation carriers under age 40 and found levels suggestive of ovarian failure in eight of them. Thus even in the absence of early menopause the premutation group appears to have the hormonal markers of ovarian failure.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis of FSH and oestradiol have been published, 13 but we also tested the two subunits of the hormone inhibin which is thought to be a good predictor of ovarian reserve. Because inhibin levels vary considerably over the follicular phase of the cycle, only sera taken on days 3, 4 or 5 were considered in the analysis.…”
Section: Hormone Analysismentioning
confidence: 99%
“…In contrast, the incidence of POF in the general population of women under 40 is estimated to be 1% [Coulam et al, 1986]. The hypothesis that POF is due to hypothalamic overstimulation has been supported by several studies documenting elevated FSH in these women [Braat et al, 1999;Murray et al, 1999]. However, whether POF in the premutation is because of a hormonal abnor- Fig.…”
Section: Neuroendocrinologymentioning
confidence: 99%
“…Vianna-Morgante et al [1999] found that premutation carriers also have an increased rate of twinning, a finding consistent with reproductive aging in which dizygotic twinning is increased, possibly due to the elevated FSH levels resulting from decreased ovarian feedback [Lambalk et al, 1998]. Several studies suggest that FSH is elevated in fragile X premutation carriers [Braat et al, 1999;Murray et al, 1999;Hundscheid et al, 2001]. However, these studies have sample sizes that are too small to evaluate hormonal changes.…”
Section: Premature Ovarian Failurementioning
confidence: 99%